Indicadores de gestión en los emprendimientos de la Dirección de Fomento productivo del Gobierno Autónomo Descentralizado de la provincia de Cotopaxi - Guacho Medina, Ingrid Sofía (2023)
Based on the fact that management indicators are essential for the good performance of an institution or organization, they indicate the current state of the established objectives, and they are also the basis for making assertive decisions. The present titling work called Management indicators in the enterprises of the Directorate of Productive Development of the Decentralized Autonomous Government of the province of Cotopaxi, has the objective of proposing management indicators in the enterprises attached to the Productive Development of the GADPC. The applied methodology is based on a quantitative approach, which allows collecting data for statistical analysis. The research is descriptive, because through it the main characteristics of the enterprises of the province and the actions carried out by the institution are examined. We work with the enterprises of the Cotopaxi Kawsay Craft Shop, and with the clients who visit the place to find out their perception of the quality of the product, these actors become the sample for the development of the investigation.